2021
DOI: 10.36941/jesr-2021-0044
|View full text |Cite
|
Sign up to set email alerts
|

Assessment for Student Success: Delivering High-Quality Modules and Improving Educational Methods in Civil Engineering Program

Abstract: There are many internal and external factors influence student success such as optimization of student support services, campus resources, teaching methods and learning outcomes achievement, and many others. Understanding student success due to the global declining quality of undergraduate engineering students is very demanding. Post training or re-educating graduates is expensive and time consuming and can be prevented by if structured educational process took a place. The aims of this study were to identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…Research has shown that an adequate evaluation of students’ learning in schools must focus on these three crucial aspects of learning ( Sönmez, 2017 ; Bitok, 2020 ; Noor et al, 2020 ). The need for holistic evaluation of students’ learning is prompted by the fact that students’ success is central to the analysis of the education process ( Afkhaminia et al, 2018 ; Abushandi, 2021 ). Studies have also established that students’ learning achievements are critical parameters for assessing whether or not education goals have been maximized ( Ali, 2013 ; Etor et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research has shown that an adequate evaluation of students’ learning in schools must focus on these three crucial aspects of learning ( Sönmez, 2017 ; Bitok, 2020 ; Noor et al, 2020 ). The need for holistic evaluation of students’ learning is prompted by the fact that students’ success is central to the analysis of the education process ( Afkhaminia et al, 2018 ; Abushandi, 2021 ). Studies have also established that students’ learning achievements are critical parameters for assessing whether or not education goals have been maximized ( Ali, 2013 ; Etor et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%